HUBUNGAN POLA MAKAN, AKTIVITAS FISIK, DAN STATUS GIZI DENGAN PROFIL LIPID PADA PASIEN WANITA MENOPAUSE YANG MENDERITA PENYAKIT JANTUNG KORONER DI POLIKLINIK JANTUNG RSPAD GATOT SOEBROTO DITKESAD - Murtikanti Parameshwari; Sri Iwaningsih (UHAMKA PRESS, 2016)
ABSTRACTContrary to popular perception, coronary artery disease is the primary cause of deathin women. Menopause is nonmodifable factor of coronary artery disease in women. Some ofresearches said that menopause inﬂuence lipid profle. Good eating patterns, enough physicalactivity, and normal nutrition status can be secondary prevention for coronary artery diseasethus have abnormal lipid profle. The purpose of this study was to know relation between eatingpatterns, physical activity, and nutrition status with lipid profle in menopause women patientswhich suffering of coronary artery disease in Heart Polyclinic of Gatot Soebroto Central ArmyHospital. Design study in this research used cross-sectional with sampling technique used ispurposive sampling and get 47 respondents. From this study can be seen that eating pattern and nutritional status had signifcant relation with total cholesterol (p=0,024, p=0,001). Eatingpattern and nutritional status also had signifcant relation with LDL cholesterol (p=0,024,p=0,001).